2021
DOI: 10.1111/epi.17044
|View full text |Cite
|
Sign up to set email alerts
|

Wearable devices for seizure detection: Practical experiences and recommendations from the Wearables for Epilepsy And Research (WEAR) International Study Group

Abstract: The Wearables for Epilepsy And Research (WEAR) International Study Group identified a set of methodology standards to guide research on wearable devices for seizure detection. We formed an international consortium of experts from clinical research, engineering, computer science, and data analytics at the beginning of 2020. The study protocols and practical experience acquired during the development of wearable research studies were discussed and analyzed during bi-weekly virtual meetings to highlight commonali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Most recently, the Wearables for Epilepsy and Research International Study Group proposed recommendations for reporting results from prospective wearable studies aimed at seizure detection. 36 These included obtaining usability challenges and user perspectives from people with epilepsy who wear the device(s). Few studies identified as part of our systematic review examined the preferences and experiences of users.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the Wearables for Epilepsy and Research International Study Group proposed recommendations for reporting results from prospective wearable studies aimed at seizure detection. 36 These included obtaining usability challenges and user perspectives from people with epilepsy who wear the device(s). Few studies identified as part of our systematic review examined the preferences and experiences of users.…”
Section: Discussionmentioning
confidence: 99%
“…reviewed all EEG recordings and annotated the timestamps of the seizures onset and offset. More details regarding the data acquisition can be found in Bruno et al [Bruno_2021].…”
Section: Methodsmentioning
confidence: 99%
“…Participants wore a variety of different wearable devices across the 2 sites; however, the only device worn by participants from both sites was a wrist-worn device (Empatica E4, Empatica Inc). The study and recording procedures were further described and discussed in the review by Bruno et al [ 29 ]. All recruited patients provided written informed consent, and the study procedures were approved by local ethics committees, the ethics committee at the University of Freiburg (538/16), and the London Fulham Research Ethics Committee (16/LO/2209; Integrated Research Application System project ID216316).…”
Section: Methodsmentioning
confidence: 99%